Redeveloping Nicosia International Airport: an extroverting Y2 group design project - Yiatros, Stylianos (My University, 2017)
This article follows the timeline of the ‘Nicosia International Airport: The Return’ Integrated Design Project which was undertaken by Year 2 students of Civil Engineering and Geomatics at the Cyprus University of Technology in Cyprus. The Nicosia International Airport was the first and main airport of the Republic of Cyprus since its independence from the British Empire in 1960. The airport remains closed since the Turkish invasion of 1974 and is located in the buffer zone administered by the United Nations Peace-keeping Force in Cyprus. In this work, the innovative aspects of a project to inspire and train engineering students are highlighted, while special attention is given to the dissemination and outreach of the project through the social media. The attracted attention of national media and the project's impact on the local society had a cyclical effect, further inspiring students to work hard and act as responsible professional engineers. ‘Nicosia International Airport: The Return’ is a case study of how an academic engineering project can have societal impact, by inspiring students, engaging practitioners from a wide spectrum of disciplines, captivating the general public and raising the profile of Civil Engineering in the society.
Keywords: Group design project; Active learning; Integrated design; Civil engineering